Multiscale modeling of composite structure-property relations : application to electron transport in carbon nanotube reinforced polymer nanocomposites - Pyrlin, Sergey (2013)
Apresentação efetuada no European Congress and Exhibition on Advanced Materials and Processes - EuroMat 2013, em Sevilha, Espanha, 2013